2020
DOI: 10.1038/s41598-020-67627-w
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Myo-inositol phosphate synthase influences plant growth and stress responses via ethylene mediated signaling

Abstract: L-myo-inositol phosphate synthase (MIPS; EC 5.5.1.4) is involved in abiotic stress tolerance, however its disruption and overexpression has also been associated with enhanced tolerance to pathogens. The molecular mechanism underlying the role of MIPS in growth, immunity and abiotic stress tolerance remains uncharacterized. We explore the molecular mechanism of MIPS action during growth and heat stress conditions. We raised and characterized the TaMIPS over-expressing rice transgenics which showed a reduced rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
1
17
0
1
Order By: Relevance
“…Our previous study with myo -inositol phosphate synthase (MIPS) suggest its role in ethylene response 50 . To further assess the role of myo -inositol (MI) in ethylene response, we analyzed the effect of myo -inositol on etiolated seedlings of Arabidopsis Col-0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study with myo -inositol phosphate synthase (MIPS) suggest its role in ethylene response 50 . To further assess the role of myo -inositol (MI) in ethylene response, we analyzed the effect of myo -inositol on etiolated seedlings of Arabidopsis Col-0.…”
Section: Resultsmentioning
confidence: 99%
“…FHY3 and FAR1 in maintenance of optimal level of myo-inositol via directly binding to the promoter of MIPS1 and activating its expression 39 . Recent study of MIPS has revealed its critical role in growth and immunity via ethylene 50 .…”
mentioning
confidence: 99%
“…Furthermore, the expression levels of some salt stress responsive marker genes, including KIN1, RD29A, RD29B, P5Cs, and COR47, were significantly more UR in overexpression of GsMIPS2 lineages than that of the wild type and the mutant atmips2. Finally, Sharma et al (2020) showed that a MIPS influenced plant growth and heat stress responses by an ethylene‐mediated signaling in wheat. Under drought conditions, ethylene causes leaf abscission and consequently reduces water loss (Oh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sharma et al (2020) showed that a MIPS influenced plant growth and heat stress responses by an ethylene-mediated signaling in wheat. Under drought conditions, ethylene causes leaf abscission and consequently reduces water loss (Oh et al, 1997).…”
Section: Transcriptionally Constitutive Enzymes Throughout the Assaymentioning
confidence: 99%
“…The role of inositol in plant hormone signaling has been driving more and more attention, and protecting the auxin to facilitated its phloem long-distance transport remains the most discussed role of inositol on auxin signaling [98]. Recent exploration of Myo-inositol phosphate (MIPS) roles in wheat growth under heat stress suggested the MIPS as essential for orchestrating the ethylene reaction and modulate plant growth and resistance to abiotic stress [99]. Additionally, Myo-inositol mediates the ROS programming cell death via ethylene-dependent and salicylic acid-dependent pathways.…”
Section: Int In Plant Hormone Distributionmentioning
confidence: 99%